The impact of substation grounding grid design parameters in non-homogenous soil to the grid safety threshold parameters - Permal N.; Osman M.; Ariffin A.M.; Ab Kadir M.Z.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric resistance; Soils; Body of knowledge; Grounding grid design; Non-uniform soils; Protection systems; Safety assessments; Standards and guidelines; Substation grounding; Two layer soil model; Electric grounding